Unraveling Melanin Biosynthesis and Signaling Networks in Cryptococcus neoformans - Lee, Dongpil (mBio, 2019)
Melanin is an antioxidant polyphenol pigment required for the pathogenicity of many fungal pathogens, but comprehensive regulatory mechanisms remain unidentified. In this study, we systematically analyzed melanin-regulating signaling pathways in Cryptococcus neoformans and identified four melanin-regulating core transcription factors (TFs), Bzp4, Usv101, Mbs1, and Hob1, required for induction of the laccase gene (LAC1). Bzp4, Usv101, and Mbs1 independently regulate LAC1 induction, whereas Hob1 controls Bzp4 and Usv101 expression. Both Bzp4 and Usv101 are localized in the cytoplasm under nutrient-rich conditions (i.e., in the presence of yeast extract-peptone-dextrose [YPD] medium) but translocate into the nucleus upon nutrient starvation (i.e., in the presence of yeast nitrogen base [YNB] medium without glucose), and Mbs1 is constitutively localized in the nucleus. Notably, the cAMP pathway is not involved in regulation of the four TFs, but the high-osmolarity glycerol response (HOG) pathway negatively regulates induction of BZP4 and LAC1. Next, we searched for potential kinases upstream of the core TFs and identified nine core kinases; their deletion led to defective melanin production and LAC1 induction. Deletion of GSK3 or KIC1 abolished induction of LAC1 and BZP4 and perturbed nuclear translocation of Bzp4. Notably, Gsk3 also regulated expression of HOB1, USV101, and MBS1, indicating that it is a critical melanin-regulating kinase. Finally, an RNA sequencing-based transcriptome analysis of the wild-type strain and of bzp4Δ, usv101Δ, hob1Δ, and mbs1Δ strains under nutrient-rich and nutrient-starved conditions revealed that the melanin-regulating core TFs govern redundant and distinct classes of genes involved in a variety of biological processes.